2020
DOI: 10.3390/su12083312
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Energy Consumption and National Output on CO2 Emissions: New Evidence from OIC Countries Using a Panel ARDL Analysis

Abstract: The issue of energy has been debated among policymakers and economists. Energy plays an important role in generating economic activities. On the other hand, it can have deleterious impacts on the environment as more carbon dioxide (CO2) emissions will be released. Most previous studies focused on total energy rather than types of energy such as oil and gas in investigating the effects of energy consumption on CO2 emissions. Therefore, this study investigates the effects of oil and gas consumption rather than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Supporting this, Wang et al (2020) argue that replacing fossil fuel with biomass energy can help to control environmental issues. In another recent study, Shaari et al (2020) find the positive impact of natural gas and energy consumption on carbon emissions of the Organization of Islamic Cooperation (OIC). Likewise, Majeed and Tauqir (2020) using extended STIRPAT modeling advocated a rise in carbon emissions as the result of energy consumption irrespective of different income categorizations of the sampled countries.…”
Section: Economic Growth Energy Consumption and Environment Nexusmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this, Wang et al (2020) argue that replacing fossil fuel with biomass energy can help to control environmental issues. In another recent study, Shaari et al (2020) find the positive impact of natural gas and energy consumption on carbon emissions of the Organization of Islamic Cooperation (OIC). Likewise, Majeed and Tauqir (2020) using extended STIRPAT modeling advocated a rise in carbon emissions as the result of energy consumption irrespective of different income categorizations of the sampled countries.…”
Section: Economic Growth Energy Consumption and Environment Nexusmentioning
confidence: 99%
“…Further, the ones who employed disaggregated data have used time-series data and CO 2 emissions . In addition, other few studies focused on various types of energy but utilize standard econometric techniques (Charfeddine (2017) along with using carbon emissions as an environmental indicator (Saboori and Sulaiman 2013;Ahmad et al 2016;Shaari et al 2020).…”
Section: Economic Growth Energy Consumption and Environment Nexusmentioning
confidence: 99%
“…Demand for fossil energy in Southeast Asia is projected to reach 80% by 2030, compared with 76% in 2020. The industrial sector continues to dominate the demand for fossil energy, with an average increase of 2.7% per year until 2035 [12]. This figure confirms that energy security is important to support regional growth.…”
Section: Introductionmentioning
confidence: 64%
“…According to the Kyoto Protocol (Kyoto Protocol to the United Nations Framework Convention on Climate Change 1997) and Paris Agreement (2015), this result shows improvements in the environment. The empirical studies of Chin et al (2018), Leitão and Balogh (2020), and Shaari et al (2020) also found a negative sign for the lagged variable of carbon dioxide emissions.…”
Section: Discussionmentioning
confidence: 85%